The Development of Critical Thinking Skills Assessment Instrument Based on Nearpod in Junior High School Science Learning - Maghfiroh, Rohmatul; Wahyuni, Sri; Ridlo, Zainur Rasyid (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Critical thinking skills are one of the skills needed in the 21st century, where to be able to assess critical thinking skills, assessment instruments are required. The aim of the research is development critical thinking skills instrument based on nearpod in junior high school science learning that meets valid, reliable, difficult, and practical criteria as well as critical thinking skills analysis. This research is a Research and Development research (R&D) with the GLAI model. The validity of the product is assessed by three validators consisting of one lecturer and two science teachers. Testing of assessment instruments was carried out on 125 grade VII students. The average product validity assessment of the three validators was 81.70% with valid criteria. Based on the field tests conducted, it is known that 10 items are valid with a reliability score of 0.602. At the difficulty level, the product has 1 easy item, 8 sufficient items, and 1 difficult item. In practicality, 97.66% was obtained with very practical criteria. In the analysis of critical thinking skills, the results of interpretation were obtained by 28.68% (very low), analysis by 31.20% (very low), inference by 43.44% (very low), and explanation by 47.80 % (low). So it is known that the critical thinking skills instrument based on nearpod in junior high school science learning was developed was valid, reliable, difficult levels, practical, and effective in measuring critical thinking skills.